Meningkatkan Kolaborasi dalam Berwirausaha di Desa Parapat Kabupaten Simalungun - Napitupulu, Junika; Gultom, Robinhot; Sianturi, Jeudi A. T. P.; Sinurat, Elperida J.; Sihite, Mislan; Purba, Jon Henri; Panggabean, Toman; Butar-Butar, Hotlan; Rajagukguk, Tiur; Normi, Siti; Melianna, Saur; Br. Saragih, Rintan; Marbun, Sondang N. B.; Panjaitan, Maludin; Silalahi, Sahat P. Remus; Panjaitan, Mangasa; Siregar, Selamat; Nadapdap, Kristanty M. N.; Winarto, Winarto; Hutabarat, Jansen (Universitas Methodist Indonesia, 2025)
This community service aims to educate that collaborating in entrepreneurship is important. This PKM took place in Parapat Village, Simalungun Regency, and the method used was by means of lectures, discussions, and question-and-answer sessions. It was explained that there are many ways to collaborate in developing a business or as an entrepreneur. In this meeting, a discussion was held so that the business being carried out and its problems were known. Finally, it was discovered that the most common problem lately was business capital and the need for local government support to support and protect the business.